"It's Only a Pastime, Really": Young People's Experiences of Social Media as a Source of News about Public Affairs. (9th September 2015) - Sveningsson, Malin
Western democracies have seen a decreased participation in activities traditionally associated with political participation. One aspect of participating politically is to keep up-to-date with what happens in society, for example, by following the news. Here, youth have been found to be less active than older generations. The decline in young people's consumption of news media does not necessarily mean that they are disinterested in news or politics; they may get their information from other sources, for example, social media. Using a qualitative multi-method approach, this article investigates how young people who are interested in civic and political issues, and who regularly access news from various sources, experience and understand, specifically, Facebook and Twitter as sources of news about public affairs. The participants appreciated the immediateness of social media news, and felt that it could provide insights into new perspectives and make news stories feel more relevant. However, it was also experienced as one-sided, fragmented, and subjective, giving a biased, or even false, image of what happens in society. The consumption of news was strongly related to the idea of being a "good" citizen. However, since the participants did not regard social media news as "real news, " their image of themselves as citizens suffered. If young people in general resemble our participants in this respect, research that asks about their news consumption runs a risk of getting answers that underestimate it, thus reinforcing the idea that young people are less interested and informed about public affairs than is actually the case.